INFLUENCE OF GLUCOSE DURING IN VITRO CULTURE ON THE SEX OF PREIMPLANTATION BUFFALO EMBRYOS - GOPIKRISHNAN1, D; SRIDEVl, P; BALASUBRAMANIAN, S; KUMANAN, K; REENA, D (The Indian Journal of Animal Reproduction, 2023)
The influence of glucose supplementation on growth rate differences between sexes of in vitro producedpreimplantation buffalo embryos was assessed by culturing presumptive zygotes in vitro with glucosesupplemented (0.5mM) and glucose free synthetic oviduct fluid (SOF) medium. Of the 220 presumptive zygotescultured in SOF medium plus glucose 48 cleaved of which, 29 were males and 19 females with a sex ratio of1.5:1. Of the 221 presumptive zygotes cultured in SOF medium minus glucose 49 cleaved of which, 25 weremales and 24 females with a sex ratio of 1: 1. In conclusion, though the supplementation of glucose resulted inan increase in number of males (29 vs. 25) this difference was not statistically significant (P = 0.87) indicatingthat it might be difficult to use this metabolic parameter as a sole criteria for sex selection of buffalo embryos.
Keywords: Glucose; Cleavage rate; Sex; Preimplantation; Buffalo embryos